Strategi Peningkatan Pembelajaran Pembinaan dan Pengembangan Bahasa Mahasiswa Program Studi Pendidikan Bahasa Indonesia FKIP Universitas Bengkulu dengan Metode Brainstorming - Rokhmat Basuki (LP4MK STKIP PGRI Lubuklinggau, 2021)
This study aims to describe the process of learning planning and improving student achievement in the coaching and development of the Indonesian language. The subjects of this study were seventh semester students of the Indonesian Language Education Study Program, FKIP Bengkulu University. The lecturer's strategy in teaching uses the brainstorming method. The results of the application of the brainstorming method showed that there were positive changes in student attitudes and behavior. This is marked by a change, in the first cycle students look happy and enthusiastic in attending lectures. In addition, students are more active and enthusiastic in participating in the entire series of lectures. The results of the study also showed an increase in the ability of coaching and language development obtained by students with satisfactory results. It was proven in the first cycle, the average score of students was 65 with details of 8 students getting very good scores or 24%. Students with good grades are 8 students or 24%, students with sufficient grades are 5 students or 14%. Then, students with less marks were 13 students or 30%. While in the second cycle the average score was 85 with details of 16 students getting very good scores or 47%, while students who got good scores were 18 students or 53%.